Study of Thermal Characteristics on Press-pack IGBT Modules - DOU Ze-chun; XIN Lan-yuan; LIU Guo-you; HUANG Rong; XU Ning-hua; WU Yi-bo (机车电传动)
Thermal characteristics of press-pack IGBT modules were studied by utilizing three kinds of approaches. The thermal model was constructed, and static thermal resistance was analyzed by computation and finite-element simulation, as well as experimental measuring approach was applied based on the calibration of temperature parameters. Result based above three methods were analyzed and compared.